Global Mindset and Sustainable Development in Africa- A Synergy - Ndum, Victor Etim; Onukwugha, Chinwe Gilean (Mediterranean Journal of Social Sciences, 2012)
Global managers and leaders have exceptionally open minds. They most often respect how differentcountries do things and they have the imagination to appreciate why they do them that way. But, they arealso incisive. They sort through the debris of cultural excuses and find opportunities to innovate .There isneed to develop the global mindset of leaders/managers, teams, individuals, and the entire Africanpopulace to enhance global sustainability. The existing scenario in Africa indicates that it does not haveenough leaders within global competencies. It is essential to identify African leadership potentials that helpto sustain competitive advantage in a dynamic global/ local environment. This advantage of course isachievable through global mindset development. The concept and idea of sustainable development iswidely accepted, and good progress has been made on sustainable development metrics; yet itsimplementation has been largely unsuccessful especially in Africa. The position of this paper is that globalmindset remains a sine qua non for sustainable development anywhere in the world. A synergy betweenglobal mindset and sustainable development has therefore been established. It was recommended amongothers, that African leaders should be more proactive and also see the development of global mindset as apriority.